Experimental paradigms in personality disorder research: a review of covered RDoC constructs, methodological issues, and future directions - Hepp, Johanna; Niedtfeld, Inga; Schulze, Lars (Personality disorders, 2023)
Studies using experimental paradigms have been paramount in research on psychopathological processes in personality disorders (PDs). We review 99 articles that report experimental paradigms and that were published between 2017 and 2021 in 13 peer-reviewed journals. We structure the study content according to the National Institute of Mental Health Research Domain Criteria (RDoC), and report details on demographic variables, experimental design, sample size, and statistical analyses. We discuss unequal representation of the RDoC domains, representativeness of the recruited clinical groups, and a lack of sample diversity. Finally, we review issues regarding statistical power and the data analytic designs that were used. Based on the literature review, we draw implications for future experimental PD research, encouraging researchers to increase the breadth of represented RDoC constructs, the representativeness and diversity of the recruited samples, the statistical power to detect between-person effects, the reliability of estimators, the adequacy of statistical methods, and the transparency of experimental research. (PsycInfo Database Record (c) 2023 APA, all rights reserved)